College Department Recommendation Expert System Web-Based Using Certainty Factor Method - Hasannah, Kholifatun; Agustin, Ninik; Aziz Zein, Mochamad Taufiqurrochman Abdul (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The choice of college major is an important decision that each prospective student must take. In the decision-making process, a genuinely accurate source of information is usually needed to avoid mistakes for prospective students when determining the college major they will take. This study implemented the certainty factor method in a website-based college central recommendation expert system to minimize and avoid these mistakes. This study uses the certainty factor method to calculate the level of confidence and uncertainty of each recommendation result given by the expert system. This system will use predetermined rules to connect input and output to provide results that match the input from the user. Based on this process, prospective students will then obtain the appropriate college major recommendation results; in this study, the recommendations are based on the types of intelligence. This study aims to help solve existing problems by building an expert system to provide colleges with significant recommendations and by implementing the certainty factor method to determine the output results of recommendations from the system. This study produces a